2015
DOI: 10.1039/c4mb00595c
|View full text |Cite
|
Sign up to set email alerts
|

Identification and molecular structure analysis of a new noncoding RNA, a sbRNA homolog, in the silkworm Bombyx mori genome

Abstract: The small noncoding group of RNAs called stem-bulge RNAs (sbRNAs), first reported in Caenorhabditis elegans, is described as molecules homologous to the Y RNAs, a specific class of noncoding RNAs that is present in vertebrates. This homology indicates the possibility of the existence of sbRNAs in other invertebrate organisms. In this work, we used bioinformatic tools and conserved sequences of sbRNAs from C. Elegans and Y RNAs to search for homologous sbRNA sequences in the Bombyx mori genome. This analysis le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 54 publications
2
7
0
Order By: Relevance
“…Recently, a family of related small non-coding RNAs, termed stem-bulge RNAs (sbRNAs), was identified in nematode worms ( Aftab et al, 2008 , Boria et al, 2010 , Deng et al, 2006 ), and an sbRNA was also described for the silkworm, B. mori ( Duarte et al, 2015 ). The genome of C. elegans contains at least 18 sbRNA genes, in addition to the related aforementioned CeY RNA gene, each with a putative RNA polymerase III promoter, with many sbRNA genes also present in other nematode species ( Boria et al, 2010 ).…”
Section: Y Rnas Are Essential Factors For the Initiation Of Chromosommentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a family of related small non-coding RNAs, termed stem-bulge RNAs (sbRNAs), was identified in nematode worms ( Aftab et al, 2008 , Boria et al, 2010 , Deng et al, 2006 ), and an sbRNA was also described for the silkworm, B. mori ( Duarte et al, 2015 ). The genome of C. elegans contains at least 18 sbRNA genes, in addition to the related aforementioned CeY RNA gene, each with a putative RNA polymerase III promoter, with many sbRNA genes also present in other nematode species ( Boria et al, 2010 ).…”
Section: Y Rnas Are Essential Factors For the Initiation Of Chromosommentioning
confidence: 99%
“…The family of small non-coding stem-bulge RNAs (sbRNAs) in nematodes has recently been shown to be homologous in structure and function to vertebrate Y RNAs ( Boria et al, 2010 , Kowalski et al, 2015 ). Small non-coding RNAs bearing similarities to vertebrate Y RNAs or nematode sbRNAs have also been reported in other eukaryotes, including the insects Anopheles gambiae ( Perreault et al, 2007 ) and Bombyx mori ( Duarte et al, 2015 ), and the lancet Branchiostoma floridae ( Mosig et al, 2007 ). Similar RNAs have also been described in some prokaryotes, including Deinococcus radiodurans ( Chen et al, 2000 ), Salmonella enterica serovar Typhimurium ( Chen et al, 2013 ), Mycobacterium smegmatis and possibly many more ( Chen et al, 2014 ).…”
Section: Introduction and Historical Overviewmentioning
confidence: 99%
“…More recent studies have revealed that Y RNAs constitute essential initiation factors for chromosomal DNA replication in human cell nuclei and that this function is conserved in vertebrates and nematodes (Kowalski and Krude, ). Y RNAs have also been identified both in Anopheles gambie (Perreault et al ., ) and Bombyx mori (Duarte Junior et al ., ). Therefore it is important to verify if Y RNAs are conserved in sciarids, and if they have a role in DNA puff gene amplification.…”
Section: Intrachromosomal Dna Amplificationmentioning
confidence: 97%
“…Y RNA are conserved molecules [11][12][13][14][15] ( Figure 1) and, in vertebrates, also their clustering is conserved [15][16][17]. A BLAST search shows that the sequence identity is higher than 90% in most vertebrates.…”
Section: Introductionmentioning
confidence: 99%